Dakwah dan Warisan Budaya Nusantara di Kalimantan Selatan: Kajian Seni Syair Sastra Madihin dalam Perspektif Semiotika Roland Barthes - Maghrobi, Muhammad Ezhar Fatih; Rifa'i, Akhmad (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2024)
The art of Madihin poetry is a rich part of the archipelago's cultural values and is an important heritage in Indonesian literary tradition. This article aims to examine the value of da'wah contained in the art of literary verse from the semiotic perspective of Roland Barthes. Originally intended for nobles or royal families, Madihin has evolved into a popular art form over time. Beyond its performative aspects, Madihin's literary dimension encapsulates numerous values. This study employs a qualitative descriptive method, utilizing Roland Barthes' semiotic analysis to interpret denotations, connotations, and myths. Semiotics provides a structured framework for understanding Madihin as a form of communication, conveying messages inherent in local art forms. The data under examination consists of Madihin poems performed by the John Tralala Group. Through interpretative techniques, the collected data is semiotically analyzed to elucidate the implicit da'wah values embedded within Madihin poetry. The research findings demonstrate the presence of worship and knowledge values that can be applied to everyday life. Moreover, the application of Roland Barthes' semiotics reveals Madihin literature's potential to influence public perceptions and artistic practices, thereby facilitating message dissemination. Syair madihin as an art can also be part of the preaching media in which there is preaching value, with research evidence that some texts of madihin poems performed by John Tralala have preaching values in the form of aqidah values, namely believing in Allah's qada and qadar, Sharia values in the form of prayer worship, the obligation to cover the aurat, and the law of marriage, and moral values in the form of mutual respect, fairness, and the obligations of a leader.